SCIENTOMATRIC ANALYSIS OF DOCTORAL THESIS IN ECONOMICS SUBMITTED AT BANGALORE UNIVERSITY WITH REFERENCE TO SHODHAGANGA WEBSITE DURING THE PERIOD FROM 2000-22 - V, Dr. Amaravathi; K., Monika; V., Vandhana (International Journal of Research -GRANTHAALAYAH, 2026)
The present study examine that there were 738(14.60%) are submitted in 2012 followed by 687(13.60%) are submitted in 2006, 1900(37.58%) references are from “Journal Articles”, 1984(39.25%) are from “Books”, 103(5.43%) are from “Indian journal of Agricultural Economics” published from “India”, 90(4.74%) with “Economic and political weekly”, 1012( 53.27%) are from “single Author”, 651(34.27% ) are from “Double Authors”, 1900 citations there were 424(22.31%) were highest from the period “2020-2010”, 413(21.74%) citations from the period “2009-1999”.